Influence of kinematic parameters on pole vault result in top junior athletes - Zagorac, N. (Collegium Antropologicum, 2013)
The aim of the research was to ascertain the level of correlation between some kinematic parameters and the result success in the pole vault, using the sample of the best European female junior athletes. A set of 11 kinematic parameters has been applied, according to the McGinnis1 model, representing a predictor assemblage of variables. The maximum height vaulted presented a criterion variable. The research was conducted at the European Junior Athletics Championships in 2009. The entities were represented by the vaults in the final part of the competition. A general hypothesis of achieving a positive correlation between the system of predictor variables and the criteria had been set, and later confirmed. The results of the pole vault regression analysis confirmed the multiple correlations between the two groups of variables. The greatest influences on the prediction of pole vault success, regarding all the analyzed kinematic parameters, were the following variables: maximum pole bend, last stride speed and time of pole bend. The results were as expected, and can be used in kinesiology practice, especially during the technique learning process in young pole vaulters, but also in development of motor abilities relevant for success in this track and field discipline.